Experimental Study on the Dynamic Performance of Water-Lubricated Rubber Bearings with Local Contact - Wu Ouyang; Xuebing Zhang; Yong Jin; Xiaoyang Yuan (Shock and Vibration)
Accurate dynamic characteristic coefficients of water-lubricated rubber bearings are necessary to research vibration of ship propulsion system. Due to mixed lubrication state of water-lubricated rubber bearings, normal test rig and identification method are not applicable. This paper establishes a test rig to simulate shaft misalignment and proposes an identification method for water-lubricated rubber bearings, which utilizes rotor unbalanced motion to produce self-excited force rather than artificial excitation. Dynamic performance tests under different conditions are operated. The results show that when rotational speed is less than 700 r/min, even if specific pressure is 0.05 MPa, it is difficult to form complete water film for the rubber bearing which was investigated, and contact friction and collision of the shaft and bearing are frequent. In the mixed lubrication, water film, rubber, and contact jointly determine dynamic characteristics of water-lubricated rubber bearings. The contact condition has a significant effect on the bearing stiffness, and water film friction damping has a significant effect on bearing damping. As for the particular investigated bearing, when rotational speed is in the range of 400~700 r/min and specific pressure is in the range of 0.03~0.07 MPa, bearing stiffness is in the range of 5.6~10.06 N/μm and bearing damping is in the range of 1.25~2.02 Ns/μm.